Biomaterials and Advanced Biofabrication Techniques in hiPSCs Based Neuromyopathic Disease Modeling - Sun, Jing; Ma, Xun; Chu, Ho Ting; Feng, Bo; Tuan, Rocky S.; Jiang, Yangzi (Frontiers in Bioengineering and Biotechnology, 2019)
Induced pluripotent stem cells (iPSCs) are reprogrammed somatic cells by defined factors, and have great application potentials in tissue regeneration and disease modeling. Biomaterials have been widely used in stem cell-based studies, and are involved in human iPSCs based studies, but they were not enough emphasized and recognized. Biomaterials can mimic the extracellular matrix and microenvironment, and act as powerful tools to promote iPSCs proliferation, differentiation, maturation, and migration. Many classic and advanced biofabrication technologies, such as cell-sheet approach, electrospinning, and 3D-bioprinting, are used to provide physical cues in macro-/micro-patterning, and in combination with other biological factors to support iPSCs applications. In this review, we highlight the biomaterials and fabrication technologies used in human iPSC-based tissue engineering to model neuromyopathic diseases, particularly those with genetic mutations, such as Duchenne Muscular Dystrophy (DMD), Congenital Heart Diseases (CHD) and Alzheimer's disease (AD).